Analisis Penyimpanan Produk Menggunakan Metode Shared Storage (Studi Kasus di PT. X) - Candrianto, Candrianto; Amalia, Wahyuni; Ramadhan, Habib Syafira (Politeknik ATI Padang, 2020)
PT. X is a company engaged in shipping services. This company has a spare part storage warehouse that is not yet effective and efficient. This can be seen from the placement of items that are not suitable and require a long time in the process of picking up goods. This study aims to redesign the layout of the storage warehouse using the shared storage method. Shared storage is a method of arranging a storage area based on the warehouse floor area by placing the items that are sent immediately closest to the door, and so on. This method uses the FIFO (first in first out) principle so that the outbound process is easier and takes less time to search for goods. Based on the processing using the shared storage method, a proposal is made to improve the layout by adding 2 storage racks arranged by product type. The previous pallet 1210 became 3234. Forging of storage racks takes into account the size of the demand, so that products with more demand are placed in the area close to the door. With this, there are no more products stored in any area, and product collection will be easier and faster.